A small open economy as a limit case of a two-country new Keynesian DSGE model: A Bayesian estimation with Brazilian data - Marcos Antonio Coutinho da Silveira (Institute for Applied Economic Research (ipea), 2015)
We build a two-country version of the DSGE model in Gali & Monacelli (2005), which extends for a small open economy the new Keynesain model used as tool for monetary policy analysis in closed economies. A distinctive feature of the model is that the terms of trade enters directly into the new Keynesian Phillips curve as a new pushing-cost variable feeding the inflation, so that there is no more the direct relationship between marginal cost and output gap that characterizes the closed economies. Unlike most part of the literature, we derive the small domestic open economy as a limit case of the two-coutry model, rather than assuming exogenous processes for the foreign variables. This procedure preserves the role played by foreign nominal frictions in the way as international monetary policy shocks are conveyed into the small domestic economy. Using the Bayesian approach, the small-economy case is estimated with Brazilian data and impulse-response functions are build to analyse the dynamic effects of structural shocks.
Keywords: E32; E52; F41; 330